DIFFERENCES IN SURFACE HARDNESS OF BOVINE ENAMEL AFTER EXPOSURE OF THEOBROMINE, ALKALOID COCOA POD EXTRACT AND ACIDULATED PHOSPHATE FLUORIDE - Tamara Yuanita; Nanik Zubaidah; Jesica Ceren (Universitas Airlangga, 2020)
Background: Acid diet could process demineralization on enamel surface. Process remineralization needed to prevent caries occurrence. The excessive fluorine usage could induce adverse side effects, therefore the development of natural resources such as theobromine and alkaloid cocoa extract as a remineralization is needed. Purpose: To discover the differences of bovine teeth enamel surface hardness after exposure to theobromine, alkaloid cocoa pod extract and acidulated phosphate fluoride. Method: Twenty-eight tooth crowns of bovine insisivus cut into the shape of the square then planted on the resin mold round shape and divided into four groups. The control group without treatment, the group I was exposed APF, the group II was exposed 1000 mg/L alkaloid cocoa pod extract, group III was exposed 200 mg/L Theobromine 200 mg/L. Surface hardness measured using Wolpert Wilson Vickers Microhardness Tool. Results: The group of theobromine produces the highest enamel surface hardness. The enamel surface hardness in alkaloid group of cocoa pod extract was higher compared to the APF group and the control group. Conclusion: The hardness surface of bovine tooth enamel after exposure to theobromine and alkaloid cocoa pod extract is harder than exposure to acidulated phosphate fluoride.